Evaluation of Performance and Heat Balance of Dry Reforming SOFC System. (30th May 2017) - Kushi, Takuto; Ohashi, Masahumi; Kato, Rei; Ito, Takuya; Inagaki, Shin; Amaha, Shinji
Abstract : The performance and heat balance of a solid oxide fuel cell (SOFC) hot box under dry and steam reforming fed by city gas, CO2 and H2 O was investigated. From the results, the heat balances of a dummy stack hot box showed an increase in stack temperature and heat loss in dry reforming compared to that of steam reforming. The evaluation of the electrical performance of SOFC hot box under dry reforming showed an electrical efficiency and power of 62.2% (LHV) and 853.1 W with satisfactory thermal self-sustainability, respectively. Its efficiency was 1.6% lower than that of steam reforming. There was no difference in stack temperature during dry reforming compared to that of steam reforming. The differences in stack temperature trends between the dummy hot box and actual hot box may have been due to an increase in the internal endothermic heat from the reformate and reduction in combustion in the actual hot box.